Effect of Unloading Equipment Rubber Tyred Gantry Crane on Productivity of Unloading PT Port of Indonesia II Port Panjang Lampung - Permata, Andre; Alfian, Rafli; Haris, Haris; Ayutia, Yola (Institut Transportasi dan Logistik Trisakti, 2023)
Panjang port is one of the ports under the management of PT. Pelabuhan Indonesia II with the main activity of serving port services and national logistics. With the reduction of loading and unloading equipment for rubber tyred gantry cranes, port productivity has decreased. This study aims to determine the effect of loading and unloading equipment rubber tyred gantry crane on loading and unloading productivity using quantitative research methods using primary data sources. The results of data processing prove that there is an effect of the number of loading and unloading equipment of rubber tyred gantry crane on loading and unloading productivity.